(untitled) (Journal of Hama University, 2021)
This research aims to determine the extent of human resource flexibility in adapting to health crisis by examining three dimensions of human resource flexibility (skill flexibility, behavior flexibility, flexibility of practices), and the research sample included(50) questionnaires distributed randomly to the heads of the divisions and departments in some hospitals and health centers of the health sector in the governorate of Hama. The most important findings were: The human resources in the health sector under study do not have sufficient flexibility to adapt to health crisis in terms of the flexibility of their behavior and the flexibility of their practices; With the exception of skill flexibility, the answers of the research sample showed that they are well available. Among the most important recommendations that were presented: The need to give workers freedom in their behavior and options to make the right decisions and avoid mistakes, and continuous changes must be made in human resources practices to achieve compatibility between the human resources system and work changes imposed by the health crisis.